Synthesis of Novel Phosphorus-Substituted Stable Isoindoles by a Three-Component Coupling Reaction of ortho-Phthalaldehyde, 9,10-Dihydro-9-oxa-10-phosphaphenanthrene 10-Oxide, and Primary Amines - Nakao, Michiyasu; Nakamura, Akihito; Takesue, Tomoyuki; Kitaike, Syuji; Ito, Hiro-O; Sano, Shigeki (SynOpen, 2023)
A three-component coupling reaction of ortho-phthalaldehyde, 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide, and various primary amines readily afforded novel phosphorus-substituted stable isoindoles in good to excellent yields. The importance of the reversible ring-opening of 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide by methanolysis in the three-component coupling reaction became apparent.
Keywords: OPA method; isoindoles; ortho-phthalaldehyde; 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide; primary amines; isoindolin-1-ones; ring-opening; methanolysis